Parkinson's disease severity levels and MDS-Unified Parkinson's Disease Rating Scale. Issue 1 (January 2015) - Martínez-Martín, Pablo; Rodríguez-Blázquez, Carmen; Mario Alvarez,; Arakaki, Tomoko; Arillo, Víctor Campos; Chaná, Pedro; Fernández, William; Garretto, Nélida; Martínez-Castrillo, Juan Carlos; Rodríguez-Violante, Mayela; Serrano-Dueñas, Marcos; Ballesteros, Diego; et al.
Abstract: Background: Severity of PD is usually assessed by means of the motor and disability-based Hoehn and Yahr staging (HY), or clinician and patient global perceptions. Scores of more detailed assessments, as the MDS-UPDRS, have not been translated to a grading that allows assignment of score sections to severity levels. The objective of the present study is to determine cut-off points for PD severity levels based on the MDS-UPDRS. Methods: International, observational study. Applied assessments were: HY, MDS-UPDRS, Clinical Impression for Severity Index, and Clinical and Patient Global Impression of Severity. The coincidence in severity level (mild, moderate, severe) of at least two clinical classifications plus the patient's gradation was considered "the criterion of severity". Cut-off values for each MDS-UPDRS subscale was determined by triangulation of: 1) percentile 90 of the subscale total score; 2) receiver operating characteristic (ROC) analysis; and 3) ordinal logistic regression (OLR) model. Results: Sample was composed of 452 consecutive PD patients without dementia, 55.3% males, age 65.1 ± 10.7 years and PD duration 8.7 ± 6.3 years. All HY stages were represented. The "criterion", classified 275 patients (60.8% of the sample) as: mild PD, 149 (54.2%); moderate, 82 (29.8%); and severe, 44 (16%). The following MDS-UPDRS cut-off points between mild/moderate and moderate/severe levels were found: Part 1: 10/11 and 21/22; Part 2: 12/13 and 29/30; Part 3: 32/33 and 58/59; and Part 4: 4/5 and 12/13. Conclusion: Cut-off points to classify PD patients as mild, moderate, or severe on the basis of their MDS-UPDRS scores are proposed. Highlights: PD severity levels based on benchmark rating scales scores are not available. The MDS-UPDRS is the comprehensive reference scale for PD. Patient and doctor agreement on the disease severity level is a consistent anchor. Based on this agreement, cut-off values for the MDS-UPDRS scores were calculated. A gradation mild, moderate, and severe for each MDS-UPDRS section is proposed.